Methane Emission and its Mitigation in Rice Fields Under Different Management Practices in Central Java - Setyanto, Prihasto (2004)
The concentration of methane (CH4), one of the greenhouse gases in the atmosphere is increasing at 1% per annum and rice soil is one of the sources that contribute to about 25% of the atmospheric CH4. This study was conducted with the objectives of (i) assessing CH4 emission from rice fields with various rice management practices in Central Java, Indonesia, (ii) identifying potential mitigation methods by taking into consideration the economic analysis of these methods, and (iii) determining the potential CH4 production and emission from rice soils of Central Java using laboratory incubation method and in-situ field measurements. Field experiments were conducted to investigate the effects of rice cultivars (Memberamo, Cisadane, IR 64 and Way Apo Buru), water management (continuous flooding 5 cm, continuous flooding 1 cm, intermittent irrigation, and pulse irrigation), and crop establishment methods (direct seeding and transplanting) on CH4 emissions using automatic chamber and continuous sampling technique. These experiments were conducted in four seasons beginning in the wet season of 2001/02 and ended in the dry season of 2003. In determining the potential CH4 production and emission from rice field of Central Java, soil types under rice were identified. In-situ measurements of CH4 fluxes from 13 soil types under rice were made and topsoil samples were incubated for laboratory incubation. There were no significant differences between cultivars in yield either through direct seeding or transplanting. Cisadane cultivar established through direct seeding emitted significantly higher amount of CH4 due to higher root and aboveground biomass than transplanting. Since no significant differences in yield between the cultivars were found in this study, Cisadane cultivar should not be used in Central Java. Emission of CH4 could also be reduced by intermittent (46%) and pulse (62%) irrigation compared to conventional continuously flooded systems. Potential CH4 production (282 – 6,408 kg ha-1) for 13 flooded rice soils in Central Java Province was significantly positively related to the in-situ field emission (107 – 799 kg ha-1). Measured CH4 emission estimated was only 16.6% of the potential CH4 production. Based on economic analysis of selected data from the field experiments, a few mitigation options could be recommended. During the wet season, for transplanted rice, Way Apo Buru gave the higher incremental benefit of CH4 mitigation technology adoption, but for direct seeded rice, Memberamo and Way Apo Buru gave the higher benefit. During the dry season, transplanted Cisadane cultivar gave higher benefit than IR 64. Also, during this season, when planted with IR 64, intermittent irrigation gave higher benefit than continuous flooding 1 cm and pulse irrigation. However, further investigation on the mitigation potentials of the management practices need to be done.